2018
DOI: 10.1002/hed.25044
|View full text |Cite
|
Sign up to set email alerts
|

Submental artery island flap with simultaneous level I neck dissection

Abstract: The submental island flap can be performed safely with a level I neck dissection for head and neck reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…In 50 patients with oral cavity malignancies undergoing submental flap reconstruction, Howard et al demonstrated occult nodal disease in level 1A in 10% of patients, without compromise to the patient's cancer care in using this flap . Authors have also published video dissections of level 1A while preserving the submental flap vasculature . In our population, level 1 was able to be dissected safely without compromising the viability of the flap, without any noted flap loss in our series.…”
Section: Discussionsupporting
confidence: 50%
“…In 50 patients with oral cavity malignancies undergoing submental flap reconstruction, Howard et al demonstrated occult nodal disease in level 1A in 10% of patients, without compromise to the patient's cancer care in using this flap . Authors have also published video dissections of level 1A while preserving the submental flap vasculature . In our population, level 1 was able to be dissected safely without compromising the viability of the flap, without any noted flap loss in our series.…”
Section: Discussionsupporting
confidence: 50%
“…Numb has been implicated in diverse array of cellular processes that contributes to cell polarity maintenance, cell migration, and EMT 812. It is widely considered to be a tumor suppressor and is involved in a variety of cancer progressions, including lung cancer,13 head and neck squamous cell carcinoma,14 prostatic cancer,15 breast cancer,16 cervical cancer,17 and so on. Colaluca et al indicated that Numb functions as a suppressor by inhibiting notch signaling and stabilizing p53 in breast cancer 16.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with plastic surgeons, oncologists are more concerned about the oncological safety of flaps, as the submental area is close to the primary site of head and neck tumors. Many researchers 10‐12 have supported the notion that pedicled submental flaps may be a reliable reconstruction option with appropriate management of level I lymph nodes. We thought that contralateral pedicled perforator flaps are more convincing to ensure their oncological safety.…”
Section: Discussionmentioning
confidence: 99%